Effect of Concept Mapping Approach on Scientific Attitude and Achievement in Science among Students with Learning Disability - Singh , Anu; Rahman, Md. Saifur (SCHOOL SCIENCE, 2025)
Students with learning disability must be equipped with means to develop their metacognitive capacities especially the ‘learning to learn’ skills for effective lifelong learning. Concept mapping is one such strategy and this study aims to determine the effectiveness of this approach on scientific attitude and achievement in science among students with learning disability. A two group, pre-test or post-test, quasi-experimental design was employed, where 35 students with learning disability of Class VIII studying in Govt. schools of Chandigarh were selected and randomly assigned to control and experimental groups. The control group (18 students, 10 Boys + 8 Girls) received conventional teaching whereas the experimental group (17 students, 8 Boys + 9 Girls) received teaching via Concept Mapping Approach for a period of 20 days. Their scores were measured on SAS-KAGS by Kaur and Gakhar and SAT by the researcher herself. Analysis of preand post-test data revealed that the Concept Mapping Approach is more effective in improving achievement in science, scientific attitude as well as retention of learned knowledge among students with learning disability as compared to conventional teaching method.